Idiopathic histaminergic angioedema without wheals: a case series of 31 patients. (13th April 2016) - Faisant, C.; Boccon‐Gibod, I.; Mansard, C.; Dumestre Perard, C.; Pralong, P.; Chatain, C.; Deroux, A.; Bouillet, L.
Summary: Idiopathic histaminergic acquired angioedema (IH‐AAE) is a common cause of recurrent angioedema without wheals. It is a mast cell‐mediated disease thought to belong to the same clinical entity as chronic urticaria (CU). The objective of this study was to describe the clinical and epidemiological characteristics of IH‐AAE patients. From 2014 to 2015, 534 patients were seen at our national reference centre for angioedema and/or urticaria. Among them, we identified 31 patients with idiopathic histaminergic acquired angioedema without wheals (IH‐AAE). Thirty‐one patients (15 men and 16 women) with a mean age of 50 years met the criteria for IH‐AAE. The average delay in diagnosis was 6·3 years. A history of allergy was found in 12 patients (38·7%), nine suffering from allergic rhinitis. The mean duration of attacks was 28·1 h. The AE attack was located in the upper respiratory tract in 54·8% of cases (17 patients). A lingual location was found in 29% of patients. Men were more likely than women to have an upper airway involvement. No intubations or admissions to intensive care units were reported. The dosage of anti‐histamines to control the symptoms was onefold the recommended dose in 51·6% of patients (16 patients), twofold in 32% (10 patients) and three–fourfold in 16·1% (five patients). IH‐AAE is characterized by an important delay in diagnosis, a frequent involvement of the upper airway and a benign course during attacks. As in CU, a trial of up to fourfold dose of H1‐anti‐histamines may be necessary to control symptoms.